1987
DOI: 10.1143/jjap.26.l706
|View full text |Cite
|
Sign up to set email alerts
|

Substitution Effect of Sr for Ba of High-Tc Superconducting YBa2Cu3O7-y Ceramics

Abstract: Single phase Y(Ba1-xSrx)2Cu3O7-y [x=0, 0.1, 0.2, 0.3, 0.4] ceramics were fabricated. In the fracture surface of the ceramics, many prism crystals were observed. Superconducting transition temperature measured by the magnetic susceptibility was linearly lowered from 94 to 84 K with increasing x from 0 to 0.4 and all the lattice constants of orthorhombic unit cell became short.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 3 publications
4
13
0
Order By: Relevance
“…For x = 0.50 it again decreases in agreement with earlier studies [2][3][4][5][6]. However, small impurity phases arises in x = 0.50 composition as increasing Sr content results in an unstable 123 phase.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For x = 0.50 it again decreases in agreement with earlier studies [2][3][4][5][6]. However, small impurity phases arises in x = 0.50 composition as increasing Sr content results in an unstable 123 phase.…”
Section: Resultssupporting
confidence: 90%
“…It can be observed that doped samples consist of slightly smaller grains than pristine sample in agreement to ref. [6]. Also the doped samples show better surface texture with lower level of porosity than pristine sample.…”
Section: Resultsmentioning
confidence: 90%
“…The c lattice parameter of the xϭ0.0 sample is smaller than that of a pure Y:123 compound without Sr substitution, in agreement with the results reported on similar samples. 21,23,24 The decreased c lattice parameter substantiates the substitution of a smaller ionic size Sr atom at the Ba site in the system. With increasing Pr concentration x, the orthorhombicity of the system decreases.…”
Section: Resultsmentioning
confidence: 72%
“…%. 21,23,24 Therefore, it is of interest to study Sr substitution in R:123, say, Y:123 along with simultaneous Pr substitution at the R site. In this article we report our findings on the superconductivity, magnetism, and structural aspects of the Y 1Ϫx Pr x Ba 1.5 Sr 0.5 Cu 3 O 7Ϫ␦ system.…”
Section: Introductionmentioning
confidence: 99%
“…The Sr doping, however, scarcely increases T c for Y124 [4], or remarkably decreases T c for YBa 2 Cu 3 O 7−δ [14][15][16][17][18], although the unit cell volume shrinks (the unit cell volume of Y124 with Sr of x=0.3 corresponds to that under an external hydrostatic pressure of about 2.4 GPa [19]). Hence, one can suspect randomness effect on the actual T c .…”
mentioning
confidence: 99%